Concepções dos licenciados em química da Universidade Federal de Sergipe (UFS) sobre a contextualização crítica numa perspectiva de ensino CTS - Santos, éverton da Paz (2015)
This study aims to investigate the interpretive demonstrations of a group of undergraduates in chemistry at the Federal University of Sergipe, on the critical context within the Science Technology and Society (STS) educational perspective, using a reading of theoretical frameworks that are committed to this approach. Also, this study aims to evaluate what was absorbed from these readings by reading and analysing textual production of undergraduates, given the expressed views and written speeches, supported by the Textual Analysis Discourse. To this end, three articles were selected that were complementary, with the same lead author.. After reading the articles, the undergraduates produced a text and answered a questionnaire that discussed the critical context and the STS approach. The results enabled the creation of categories and emerging categories from the analysis of data collected through the discursive manifestations of undergraduates, which can frame and categorize these speeches, which distanced themselves from the concept of critical contextualization, championed by the author of the text and by the author of this study, pointing to a still very timid advance on the intervention performed, as reading and writing practice is undervalued in the education of these undergraduates.